1994
DOI: 10.2172/10102146
|View full text |Cite
|
Sign up to set email alerts
|

MELCOR 1.8.2 assessment: Aerosol experiments ABCOVE AB5, AB6, AB7, and LACE LA2

Abstract: for the United Stater Department of Energy under Contract DE-ACOeQ4ALApproved for public rele ution is unlimited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…[26] MELCOR models condensation/evaporation effects on aerosol particle size, but does not include any model for such hygroscopic effects. The lack of such a model has been noted in previous MELCOR assessments of aerosol behavior in humid atmospheres [3,27].…”
Section: Condensat Ion/evaporat Ion On Aerosolsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] MELCOR models condensation/evaporation effects on aerosol particle size, but does not include any model for such hygroscopic effects. The lack of such a model has been noted in previous MELCOR assessments of aerosol behavior in humid atmospheres [3,27].…”
Section: Condensat Ion/evaporat Ion On Aerosolsmentioning
confidence: 99%
“…The lack of such a model has been noted in previous MELCOR assessments of aerosol behavior in humid atmospheres [3,27]. However, in our reference calculation, condensation/evaporation was specified to take place only on water aerosols and not on all aerosols present (as in the code default), to avoid other modelling problems.…”
Section: Evaporat Ion/condensat Ionmentioning
confidence: 99%
“…There have been several researches on comparison and validation of these computer codes with experiments, including Phébus FPT and ABCOVE & LACE experiments. For example, L. Herranz et al [5] validated CONTAIN 2.0 using Phébus FPT1 experiment and J. Souto et al [18] did the validation of MELCOR 1.8.2 code using ABCOVE & LACE experiments. G. Gyenes et al [19] validated the CPA module (Containment Package implemented in the European integral code ASTEC) using Phébus FPT0, FPT1, and FPT2 experiments.…”
Section: Introductionmentioning
confidence: 99%
“…A number of experimental studies have been conducted to physically and chemically characterize Na compounds in aerosols. Some of the most outstanding facilities involved in this investigation are: CSTF in U.S. (Hilliard et al, 1985;Postma and Owen, 1980;Souto et al, 1994), FAUNA in Germany (Cherdron and Charpenel, 1985;Cherdron and Jordan, 1980) (Subramanian et al, 2009;Subramanian and Baskaran, 2007), NSPP in U.S. (Adams et al, 1979) and ESMERALDA in France (Jordan et al, 1988).…”
Section: Aerosol Characterization and Size Distributionmentioning
confidence: 99%
“…The Lhiaubet et al benchmark concluded that aerosol codes were adequate for pool fire conditions in the sense that they tended to be conservative by overestimating (but not massively) the suspended aerosol concentration. Later, Souto et al (1994) demonstrated that the aerosol transport mechanisms were accurate enough as long as particles and particle-particle interactions were well described by modelling the CSTF experiments with the MELCOR 1.8.2 code.…”
Section: Frame Of the Thesis 14mentioning
confidence: 99%